2014
DOI: 10.1111/str.12091
|View full text |Cite
|
Sign up to set email alerts
|

50th Anniversary Article: The Origin and Management of Residual Stress in Heat‐treatable Aluminium Alloys

Abstract: The presence of macroscopic residual stresses in heat-treatable aluminium alloys can give rise to machining distortion, dimensional instability and increased susceptibility to in-service fatigue and stress corrosion cracking. This paper presents and reviews details about the residual stress magnitudes and distributions introduced into wrought aluminium alloys by the thermal operations associated with heat treatment. Experimental measurement data and the results of finite element analysis are presented and disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 53 publications
3
50
0
Order By: Relevance
“…However, it is not negligible as revealed by the 50 MPa difference between simulations with and without precipitation at the surface. Robinson et al (2014) measured ca. 180 MPa compressive stress at the surface of a 16 mm thick AA7010 block.…”
Section: Thermomechanical Model Of Quenchingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not negligible as revealed by the 50 MPa difference between simulations with and without precipitation at the surface. Robinson et al (2014) measured ca. 180 MPa compressive stress at the surface of a 16 mm thick AA7010 block.…”
Section: Thermomechanical Model Of Quenchingmentioning
confidence: 99%
“…However, high thermal gradients through the thickness cause non-homogeneous plastic strain resulting in residual stresses (RS) after quenching. Robinson et al (2014) showed that surface RS measured by X-ray diffraction on AA7010 cold-water-quenched rectangular blocks increase when the thickness increases from 16 mm to 124 mm. Quenching is thus followed by a stress relief, as explained by Jeanmart and Bouvaist (1985), that reduces residual stresses by a factor of approximately 10 as shown by Boyer and Boivin (1985).…”
Section: Introductionmentioning
confidence: 99%
“…Thermal gradients decrease from the surface to the center and give rise to residual stresses (RS) [6]. The magnitude of the as-quenched RS can be very high and even exceed the as-quenched strength of the materials [6,7]. In the case of Al-Zn-Mg-Cu alloys, the high as-quenched RS are caused by the formation of fine hardening precipitates that form during quenching of large components and thereby increase the yield strength of the material [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The slower quench conditions (Q2-Q4) refers to cooling conditions that are typical between the surface and center of larger forgings [13,20]. The cooling conditions end at 100°C since large components are often quenched in boiling water to control RS [6]. Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation